Article 2: Longitudinal study assessing the one-year effects of supervision performance assessment and recognition strategy (SPARS) to improve medicines management in Uganda health facilities - Birna Trap; Richard Musoke; Anthony Kirunda; Martin Olowo Oteba; Martha Embrey; Dennis Ross-Degnan (Taylor & Francis Group, 2018)
Background In late 2010, Uganda introduced a supervision, performance assessment, and recognition strategy (SPARS) to improve staff capacity in medicines management in government and private not-for-profit health facilities. This paper assesses the impact of SPARS in health facilities during their first year of supervision. Methods SPARS uses health workers trained as Medicines Management Supervisors (MMS) to supervise health facilities and address issues identified through indicatorbased performance assessment in five domains: stock management, storage management, ordering and reporting, prescribing quality, and dispensing quality. We used routine data generated during SPARS visits to 1222 health facilities to evaluate performance changes during the first year of supervision as well as the time until achieving an adequate score in this period. We also explored variables related to facilities, MMS, and intensity of implementation as predictors of performance improvement and time until achieving an adequate score. Results Health facilities received an average of 3.4 MMS visits during the first year of supervision, with an average of 88 days between visits; each MMS implemented a median of 28 visits per year. Overall SPARS scores (maximum of 25) improved by 2.3 points (22.3%) per visit from a mean baseline score of 10.3. The adjusted improvement in overall SPARS score was significantly higher in primary health care facilities (2.36) versus higher-level health facilities and hospitals (2.15) (p = 0.001). The incremental improvement was highest at visit 2, with decreasing but continuing positive gains in subsequent visits. The adjusted mean incremental improvement per visit was highest in the prescribing quality domain, followed by dispensing quality, ordering and reporting, stock management, and storage management. Adjusted improvement in SPARS scores varied by region, year of implementation, and facility ownership. After one year of SPARS, 22% of facilities achieved an adequate score of 18.75 (75% of maximum score). Conclusions SPARS was effective in building health facility capacity in medicines management, with a median overall improvement of almost 70% during the first year. The greatest improvements occurred in prescribing quality and at lower levels of care, although the highest level of performance was achieved in storage management. We recommend broad dissemination of the SPARS approach in all Ugandan health facilities as well as in other countries seeking a practical strategy to improve medicines management performance.